Comparison of etorphine-midazolam and etorphine-azaperone for African buffalo (Syncerus caffer) immobilisation - Zeiler, Gareth Edward (University of Pretoria, 2021)
Mini Dissertation (MMedVet (Anaesthesiology))--University of Pretoria, 2020.